Cloning, sequence determination, and expression of a 32-kilodalton-protein gene of Mycobacterium tuberculosis. - Borremans, M (1989)
We describe the identification of the gene encoding an immunodominant 32-kilodalton (kDa) protein of Mycobacterium tuberculosis. The 32-kDa antigen is abundantly secreted into the culture supernatant of a variety of mycobacteria and appears to be a major stimulant of cellular and humoral immunity against mycobacteria. Recombinant clones expressing a 140- or 125-kDa beta-galactosidase fusion protein reactive with rabbit polyclonal anti-32 kDa protein serum were detected. The corresponding DNA sequence contains a 1,008-base-pair coding region. The deduced amino acid sequence corresponds to a 336-residue protein including the previously determined NH2-terminal sequence of the 32-kDa protein (J. De Bruyn, K. Huygen, R. Bosmans, M. Fauville, R. Lippens, J. P. Van Vooren, P. Falmagne, M. Weckx, H. G. Wiker, M. Harboe, and M. Turneer, Microb. Pathog. 2:351-366, 1987). Upstream of this NH2-terminal region, the gene codes for a signal peptide required for the secretion of a 294-amino-acid-long mature protein. A putative promoter sequence could be located upstream of the open reading frame. Comparison of the M. tuberculosis 32-kDa antigen with the Mycobacterium bovis BCG alpha-antigen (K. Matsuo, R. Yamaguchi, A. Yamazaki, H. Tasaka, and T. Yamada, J. Bacteriol. 170:3847-3854, 1988) revealed 73.8% homology between DNA sequences and 72.8% homology between amino acid sequences (signal and mature protein). Finally, the 140-kDa fusion protein could selectively be recognized by human tuberculous sera. This result confirms our previous finding that the 32-kDa antigen could be a valuable tool for the serological diagnosis of tuberculosis. Moreover, the availability of recombinant proteins opens perspectives for the localization of relevant B- and T-cell epitope regions on the 32-kDa antigen.